An Analysis of Clinical Handover Miscommunication Using a Language and Social Psychology Approach. (December 2015) - Watson, Bernadette M.; Manias, Elizabeth; Geddes, Fiona; Della, Phillip; Jones, Dorothy
Clinical handover is a key communication event in patient care and a major contributing factor in adverse events in hospitals. Current research on handover emphasizes communication skills training. We investigate the intergroup context and systemic factors of the hospital environment that also affect handover. We explore the responses of 707 health professionals about handover practice. We invoke Coupland and colleagues' integrative model of "miscommunication" to interpret these. Results support the model. Responses reflect a lack of communication competency, intergroup group relations, and the hidden ideology of the health care system. Health professionals in hospitals are often unaware of the socio-structural element in health care and so cannot bring about cultural change. We suggest that clinicians work with communication and interdisciplinary scholars to bring about system improvement.